Detection of human papillomavirus DNA in semen from patients with intrameatal penile warts. Issue 6 (December 1989) - Green, J; Monteiro, E; Gibson, P
Abstract : Fifteen semen specimens from 10 men with intrameatal penile warts attending a genitourinary clinic were tested by Southern blot hybridisation for the presence of human papillomavirus (HPV) DNA. Five specimens were positive for HPV types 6/11. This observation may have implications for screening of semen used for artificial insemination by donor.